Proceedings of the Forty-Second ACM Symposium on Theory of Computing 2010
DOI: 10.1145/1806689.1806792
|View full text |Cite
|
Sign up to set email alerts
|

Graph expansion and the unique games conjecture

Abstract: The edge expansion of a subset of vertices S ⊆ V in a graph G measures the fraction of edges that leave S. In a d-regular graph, the edge expansion/conductance Φ(S) of a subset S ⊆ V is defined as Φ(S) = |E(S,V \S)| d|S| . Approximating the conductance of small linear sized sets (size δn) is a natural optimization question that is a variant of the well-studied Sparsest Cut problem. However, there are no known algorithms to even distinguish between almost complete edge expansion (Φ(S) = 1 − ε), and close to 0 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
236
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(240 citation statements)
references
References 30 publications
1
236
0
Order By: Relevance
“…In the work of Raghavendra and Steurer (2010), the Small Set Expansion (SSE) Conjecture was introduced, and it was shown that it implies the UGC, and that the SSE Conjecture follows if one assumes that the UGC is true for somewhat expanding graphs. In follow-up work by Raghavendra et al (2012), it was shown that the SSE Conjecture is in fact equivalent to the UGC on somewhat expanding graphs, and that the SSE Conjecture implies NP-hardness of approximation for balanced separator and MLA.…”
Section: The Small Set Expansion Conjecturementioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Raghavendra and Steurer (2010), the Small Set Expansion (SSE) Conjecture was introduced, and it was shown that it implies the UGC, and that the SSE Conjecture follows if one assumes that the UGC is true for somewhat expanding graphs. In follow-up work by Raghavendra et al (2012), it was shown that the SSE Conjecture is in fact equivalent to the UGC on somewhat expanding graphs, and that the SSE Conjecture implies NP-hardness of approximation for balanced separator and MLA.…”
Section: The Small Set Expansion Conjecturementioning
confidence: 99%
“…Similarly, the approximability of many related graph layout problems is also unresolved, including Minimum Cut Linear Arrangement and Interval Graph Completion. In this paper, we make an important step to resolve this problem by showing that Treewidth, Pathwidth, and a host of related graph layout problems are hard to approximate to within any constant factor, under the Small Set Expansion (SSE) conjecture (Raghavendra & Steurer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sparsest small set problem has been shown to be closely related to the Unique Games problem (see [RS10,ABS10] ). Recently, Arora et.…”
Section: Generalizations Of Sparsest Cutmentioning
confidence: 99%
“…We don't describe it here, but do point out that it is hypercube based and the fact that the (integral) optimum is low is related to the fact that small subsets of a boolean hypercube are almost fully expanding. This partly motivates Theorem 5.2 giving a connection between the UGC and the Small Set Expansion problem [94].…”
Section: Integrality Gapsmentioning
confidence: 65%
“…Raghavendra and Steurer [94] give a reduction from the Small Set Expansion problem to the Unique Game problem. Whereas we have several reductions from the Unique Game problem to other optimization problems, this is the first reduction in the other direction.…”
Section: The Small Set Expansion Problemmentioning
confidence: 99%